2023
DOI: 10.1039/d3qi00668a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus doped hierarchical porous carbon: an efficient oxygen reduction electrocatalyst for on-site H2O2 production

Abstract: Electrochemical oxygen reduction reaction through a two-electron process (2e- ORR) has been considered a promising alternative for on-site hydrogen peroxide (H2O2) production. Nevertheless, exploring low-cost and stable electrocatalysts with higher...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Previous experimental and theoretical studies have revealed that using O 2 or N 2 O as an oxidant in CO oxidation can lead to rate-limiting steps with substantial energy barriers, ,,,, exemplified by the Rh 1 /PTA catalyst with a barrier of 41.0 kcal/mol . In light of the recent advancements in two-electron oxygen reduction reactions, which have accelerated H 2 O 2 production, H 2 O 2 emerges as a greener and more efficient alternative to O 2 for low-temperature CO oxidation. The critical role of solvents in selective CO oxidation has been well-established, prompting investigations into CO oxidation activities in various common solvents beyond the gas phase. , Fortunately, the solubility of POMs in both organic and aqueous solvents allows their application in a wide range of catalytic systems, enhancing both homogeneity and heterogeneity in catalysis. , …”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental and theoretical studies have revealed that using O 2 or N 2 O as an oxidant in CO oxidation can lead to rate-limiting steps with substantial energy barriers, ,,,, exemplified by the Rh 1 /PTA catalyst with a barrier of 41.0 kcal/mol . In light of the recent advancements in two-electron oxygen reduction reactions, which have accelerated H 2 O 2 production, H 2 O 2 emerges as a greener and more efficient alternative to O 2 for low-temperature CO oxidation. The critical role of solvents in selective CO oxidation has been well-established, prompting investigations into CO oxidation activities in various common solvents beyond the gas phase. , Fortunately, the solubility of POMs in both organic and aqueous solvents allows their application in a wide range of catalytic systems, enhancing both homogeneity and heterogeneity in catalysis. , …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Recently, transition metal phosphides (TMPs) have sparked tremendous investigations in the fields of ORR and ZABs. 18 Charge-rich P sites with lone pair electrons in 3p and 3d orbitals can restrict electron delocalization, which induces local charge density, mediates surface state density, and ultimately effectively regulates the electronic configuration and adsorption property of the active center. 19,20 Remarkably, transition metal atoms (such as Fe, Co, and Ni) have analogous 3d orbitals and lower crystal field activation energies, and once M-P bonds are formed, TMPs may be endowed with enhanced thermal and chemical characteristics, contributing to the ORR.…”
Section: Introductionmentioning
confidence: 99%